Typhoid fever: hurdles to adequate hand washing for disease prevention among the population of a peri-urban informal settlement in Fiji - Mosese Salusalu; Jacob Kool; Judith McCool; James Greenwell (World Health Organization Regional Office for the Western Pacific, 2013)
Problem/context: The Pacific island nation of Fiji Islands has high rates of endemic typhoid fever which is difficult to diagnose and often underreported. However, the majority of cases are preventable through use of safe water; adequate sanitation; vaccination; and, most sustainable of all, simple hygienic behaviour, such as hand washing with soap (HWWS). Despite many attempts by public health authorities, little progress has been made in the area of environmental adaptation and behaviour change. Action: To explore perceptions of typhoid fever risk among urban squatters and behavioural determinants surrounding HWWS, indigenous Fijians living in informal settlements with high typhoid fever incidence were invited to participate in focus group discussions. In-depth interviews were conducted with community leaders. Outcome: Perceptions of typhoid fever suggest confusion about risk factors, symptoms and communicability. Environmental barriers for hand washing were related to water and soap access. Standard social marketing approaches have been trialled with little clear evidence of impact. Despite this, we continue to advocate for the social and cultural determinants of typhoid prevention to remain central to future public health strategies. Discussion: Despite behaviour change being notoriously difficult, we argue that community-driven behaviour adaptation initiatives based on sound epidemiological evidence and health communication theory are likely to have significant impact and greater likelihood of sustainability.